2001
DOI: 10.1038/sj.leu.2402107
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of chemokine receptors in B cell malignancies

Abstract: Chemokines are a family of 8-10 kDa proteins with a wide range of biological activities including the regulation of leukocyte trafficking, modulation of haemopoietic cell proliferation and adhesion to extracellular matrix molecules. Using a panel of chemokine receptor-specific monoclonal antibodies (MoAb) in a multicolour flow cytometry approach we analysed the expression of the lymphocyte-associated chemokine receptors CXCR4, CXCR5, CCR5 and CCR6 in B cell acute lymphoblastic leukaemia (precursor B-ALL; six c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 24 publications
10
90
0
Order By: Relevance
“…In line with our results on the expression of CXCR4 on primary MM cells and MM cell lines is a recent study by Dü rig et al, 23 where they described that primary MM cells do express CXCR4. However, in that study they did not investigate the migratory response of the cells to SDF-1.…”
Section: Figuresupporting
confidence: 93%
See 2 more Smart Citations
“…In line with our results on the expression of CXCR4 on primary MM cells and MM cell lines is a recent study by Dü rig et al, 23 where they described that primary MM cells do express CXCR4. However, in that study they did not investigate the migratory response of the cells to SDF-1.…”
Section: Figuresupporting
confidence: 93%
“…8 In contrast to a number of B cell tumors, including chronic lymphocytic leukemia (CLL), 23,24 we could not detect any expression of CXCR5 mRNA or protein in MM cells. The difference in CXCR5 expression on B-CLL and MM cells is likely due to the fact that these cells represent different stages of differentiation within the B cell lineage.…”
Section: Figurementioning
confidence: 58%
See 1 more Smart Citation
“…149 High expression of CXCR4 has also been shown in mantle cell lymphoma and B-cell acute lymphoblastic and chronic lymphocytic leukemia cells. 150 The present study shows strong expression of CXCR5 and CXCR4 on PIOL cells and of BLC on RPE cells. The findings of BLC that functions as a homing chemokine expressed in RPE and CXCR5 that is detected in PIOL cells may be one important mechanism for tumor cell homing and localizing between the RPE and Bruch's membrane in the eye.…”
Section: Piol Homing May Be Related To Expression Of Surface Chemokinsupporting
confidence: 58%
“…In addition, it has been demonstrated that corresponding receptors of these cytokines are expressed by MM cells and therefore these cytokines can play a role in MM. [17][18][19][20][21][22][23][24][25][26][27][28] Nevertheless, with exception of IL-6, the precise role of these cytokines in MM is still unclear.…”
Section: Introductionmentioning
confidence: 99%